The Problem of Lexical Cohesion and Lexical Structure in Bantu Classes (Part 2) - Assibi Apatewon Amidu (Nordic Journal of African Studies, 1999)
Bresnan and Mchombo (1995) propose that lexical words may be adequately tested for lexicality, i.e. what they call “lexical integrity”, by means of five tests: extraction, conjoin ability, gapping, inbound anaphoric islands, and phrasal recursivity. The writers claim that, "Alternative concord is in fact a special case of phrasal recursivity, and it makes a compelling case for the syntactic analysis of the noun class markers by showing their lack of lexical integrity." (p. 197)